Prevalence and Associated Factors of Cognitive Impairment among Elderly in Watphleng District, Ratchaburi Province - Imarb, Chawanon (Journal of Health Science of Thailand, 2019)
The cognitive impairment in the elderly negatively affects their memory capacity, hinders them from learning new things, deviates their concentration or decision-making ability which then may troubles their daily living condition. Around 80.0% of people with cognitive impairment will likely continue to suffer with dementia. This study aimed to study prevalence and factors associated with cognitive impairment in the elderly in Wat Phleng District, Ratchaburi Province. The participants were 250 elderly people aged 60 years and over, male and female, residing in Wat Phleng District They were selected by simple random sampling based on the proportion classified by their affiliated district. Constructed questionnaires were used to collect data. The risk factors of cognitive impairment were analyzed and compared between cognitive impaired and non-cognitive impaired groups using Fisher’s excat test and odd ratio. The factors with p-value less than 0.05 were then analyzed to identify the relationship among multivariate factors by multiple logistic regression. The study indicated that factors associated with the occurrence of cognitive impairment in the elderly were those aged 80 years and over held the risk at 11.1 times (p<0.05), non-physical activity during free time held the risk at 4.8 times (p<0.05), and joining very few social activities held the risk at 6.1 times (p<0.05). Therefore, closely monitoring the occurrence of cognitive impairment of the elderly in these risk groups is necessary.